Self Happines Sebagai Media Menaggulangi Self Harm: Studi Kasus Mahasiswa Ftik Iain Palangka Raya - Ayu Lestari; Ajahari Ajahari; Surawan Surawan (Journal on Education, 2025)
Building self-happiness needs to be done in order to overcome self-harming behavior. This is because happiness is the goal that everyone wants to achieve in life. Therefore, the purpose of this study is self-happiness as a medium to overcome self-harm among students. The type of research is qualitative with a case study approach, while the subjects of this study were 5 students of FTIK IAIN Palangka Raya. Data collection techniques using observation, in-depth interviews and documentation and data validation techniques using source triangulation. The results of this study indicate that self-happiness can overcome self harm among students by 84.55% including the effective category, this is because by building positive expectations, self-affirmation, positive emotions and self-adjustment can overcome self harm.